Cloud-Based Approach for Water Quality Monitoring: A Review - Zahari N.M.; Saeed A.S.S.; Zawawi M.H.; Roslin N.T.; Aziz N.A.; Nurhikmah F. (Springer Science and Business Media Deutschland GmbH, 2023)
Controllers; Internet of things; Monitoring; Cloud-based; Communicationtechnology; Current system; Essential equipments; Monitoring system; Review papers; Sensor technologies; Smart System; Water quality information; Water quality monitoring; Water quality